La contribución de los tribunales eclesiásticos a la familia en la alocuciones de los Sumos Pontífices a las Rota Romana - López de Guerñu, Roberto Serres ("Iustitia et iudicium" ; 3, 2010)
When pastoral care of the family is thought of, it is unusual to take into consideration the service of ecclesiastical tribunals. Rather, their activity appears to many as something of an excluse and technical nature, related only lightly to the life of the Church and the acceptance of God's plan on marriage and family. The addresses of the Popes to the Roman Rota show how the activity of this tribunal constitutes and indispensable contribution to the service to both marriage and family since it helpos to understand more about the nature of marriage